Hladno valjani trakovi iz maloogljičnih jekel - Bricelj, Erika (Materiali in tehnologije, 2000)
The differences in mechanical properties and microstructures of cold-rolled sheets made from low-carbon steels with: -lower content of interstitial elements, -interstitial free steels with additions of Nb and/or Ti are presented.
Keywords: jekla; trakovi; valjanje